Kekerasan Struktural terhadap Orang Lanjut Usia sebagai Hasil dari Konstruksi Sosial yang Merendahkan tentang Lansia (Studi Pada Penghuni Panti Werdha Di Bekasi) - Shinta Julianti (Jurnal Kriminologi Indonesia, 2013)
This research discusses about structural violence experienced by the elderly. This research sees the social vulnerability experienced by the elderly as a result of the social construction degrading on elderly which is formed in the society structure. In addition, the poverty experienced by the elderly, also increasingly provides more risk of vulnerability for them thus experiencing various treatments that are harmful and sufferable include, the social exclusion and elder abuse. This matter results in some losses of their human rights which is interpreted as a structural violence. The elderly residents of elderly nursing home in Bekasi experiencing structural violence are the subject of this research, which their experience was obtained through in-depth unstructured interviews and the observation of participation applied to analyze in this research. Critical approach had been applied for viewing how the structural violence experienced by the elderly residents of elderly nursing home in Bekasi as a result of the social construction degrading on elderly.